EFECTO DE Trichoderma sp EN EL COMBATE DE Pratylenchus spp EN EL CULTIVO DE BANANO VARIEDAD GRAN WILLIAM (Musa paradisiaca) - Palacios Moran, Mauro Danilo (2023)
Nematodes cause the greatest damage in production. Economic losses worldwide are estimated at 20%, but in local conditions losses of 40 to 50% have been detected. As an alternative control Trichoderma are used against pathogenic organisms, due to the production of industrial enzymes such as anthraquinone pigments and secondary metabolites (MS), antibiotics and plant growth promoter (PGP) their ability to parasitize, control and destroy phytonematodes. This research was carried out at the facilities of the Campus “La María”, of the Universidad Técnica Estatal de Quevedo.